Bargaining with baseball labor relations in an age of prosperous turmoil - Gould, William B. (McFarland & Co., 2011)
"This study considers the full, 140-year sweep of labor-management relationships and conflict, exploring player-owner disputes, the development of free agency, the collective bargaining process, and the racial integration of baseball, among other topics. It concludes with a discussion of the "steroids era," the problem with maintaining Jackie Robinson's legacy in the 21st century, and globalization"--Provided by publisher.